Dual‐frequency impedance matching networks based on two‐section transmission line. Issue 10 (13th July 2017) - Maktoomi, Mohammad A.; Yadav, Ajay P.; Hashmi, Mohammad S.; Ghannouchi, Fadhel M.
Abstract : In this study, a practical and useful dual‐frequency property of two‐section transmission line (TSTL) terminated into a real impedance is reported. Moreover, to demonstrate some of its potential applications for the performance enhancement in dual‐frequency impedance transformation problems, modified L‐ and T‐type dual‐frequency matching networks are presented. Specifically, the property is used to modify the conventional L‐type matching network to improve its transformation‐ratio and frequency‐ratio performance. Furthermore, improvement in conventional dual‐frequency T‐type matching network is also demonstrated through the incorporation of the TSTL. All the results are analytical and in closed form with simple design equations. For validation, prototypes of the proposed L‐ and T‐type matching networks operating concurrently at 1 GHz/1.45 GHz and 1 GHz/2 GHz, respectively, are designed and fabricated on FR‐4 substrate. The obtained simulated and measured results clearly exhibit the usefulness of the proposed design schemes.